2020
DOI: 10.1021/acschemneuro.0c00156
|View full text |Cite
|
Sign up to set email alerts
|

Astragalin Exerted Antidepressant-like Action through SIRT1 Signaling Modulated NLRP3 Inflammasome Deactivation

Abstract: Inflammation plays a key role in the pathogenesis of depression and antidepressant therapies. Astragalin (AST) is a bioactive flavonoid that possesses an anti-inflammatory property. However, the antidepressant action of astragalin has not been addressed. In this study, we explored the antidepressant effects of astragalin and its underlying mechanism. Our results showed that AST significantly improved the behavioral defects in chronic unpredictable mild stress (CUMS) model, promoted SIRT1 expression, and decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Moreover, emerging data have shown that plant-derived compounds can exert neuroprotective effects that prevent neurological disorders in depression. For instance, ganoderic acid A [ 227 ], asperosaponin VI [ 228 ], 20( S )-protopanaxadiol [ 229 ], scutellarin [ 230 ], astragalin [ 231 ], hesperidin [ 232 ], 5- O -methylvisammioside [ 233 ], ginkgolide B [ 234 ], leonurine [ 235 ], ferulic acid [ 236 ], and (+)-sesamin [ 69 ] were found to inactivate microglia in stress-induced depression models. Recent information concerning the antidepressant activity of phytochemicals through regulation of microglial polarization is illustrated in Table 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, emerging data have shown that plant-derived compounds can exert neuroprotective effects that prevent neurological disorders in depression. For instance, ganoderic acid A [ 227 ], asperosaponin VI [ 228 ], 20( S )-protopanaxadiol [ 229 ], scutellarin [ 230 ], astragalin [ 231 ], hesperidin [ 232 ], 5- O -methylvisammioside [ 233 ], ginkgolide B [ 234 ], leonurine [ 235 ], ferulic acid [ 236 ], and (+)-sesamin [ 69 ] were found to inactivate microglia in stress-induced depression models. Recent information concerning the antidepressant activity of phytochemicals through regulation of microglial polarization is illustrated in Table 2 .…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that Astragaline displayed antidepressant dependent on SIRT1-activation modulated NLRP3 inflammasome deactivation. [232] 4.13.14. Arctiin Arctiin (209, Figure 27) was a major bioactive component derived from Fructus arctii and possessed neuroprotective and anti-inflammatory activities.…”
Section: Higenaminementioning
confidence: 99%
“…These results indicated that Astragaline displayed antidepressant dependent on SIRT1‐activation modulated NLRP3 inflammasome deactivation. [ 232 ]…”
Section: Advances In Small Molecules With Antidepressant Activitiesmentioning
confidence: 99%
“…• Astragalin /À ! anti-depressive activity via SIRT1 signaling pathway (Tong et al, 2020) • Apigenin /FST, TST and sucrose preference test, western blot analysis ! anti-depressant activity via promoting autophagy (AMPK/mTOR signaling pathway) (X.…”
Section: Flavonoidsmentioning
confidence: 99%